MiR-208a-3p functions as an oncogene in colorectal cancer by targeting PDCD4. Issue 4 (16th April 2019) - Wu, Henglan; Xu, Lele; Chen, Yaou; Xu, Chunfang
Abstract : Accumulating evidences have shown microRNAs (miRNAs) play important roles in the progression of human cancers including colorectal cancer (CRC). However, the biological function and molecular mechanism of miRNAs in CRC still remains to be further investigated. Using microarray, we found and confirmed that miR-208a-3p was up-regulated in CRC tissues. Its high expression was statistically associated with distant metastasis and TNM stage. Functional assays revealed inhibition of miR-208a-3p suppressed proliferation, invasion and migration, and induced cell apoptosis of CRC cells. Moreover, we identified programmed cell death protein 4 (PDCD4), a well-known tumor suppressor, is a direct target of miR-208a-3p. We also found that overexpression of PDCD4 suppressed cell proliferation, invasion, and migration. Importantly, silencing of PDCD4 efficiently abrogated the promoting effects on CRC cells proliferation, invasion, and migration caused by inhibition of miR-208a-3p. Our findings confirmed the oncogenic role of miR-208a-3p via targeting PDCD4 in CRC, identifying miR-208a-3p as a potential diagnosis and therapeutic biomarker for CRC.